2024
DOI: 10.3389/fcvm.2023.1287434
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for major adverse cardiovascular events after percutaneous coronary intervention: a systematic review

Wenqi Deng,
Dayang Wang,
Yandi Wan
et al.

Abstract: BackgroundThe number of models developed for predicting major adverse cardiovascular events (MACE) in patients undergoing percutaneous coronary intervention (PCI) is increasing, but the performance of these models is unknown. The purpose of this systematic review is to evaluate, describe, and compare existing models and analyze the factors that can predict outcomes.MethodsWe adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 during the execution of this review. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It is worth noting that these studies only observed the ECG for a period of 120 min. Nevertheless, future research and external validation might include these easily measured ECG parameters in predictive models, where their real predictive power would be obtained [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that these studies only observed the ECG for a period of 120 min. Nevertheless, future research and external validation might include these easily measured ECG parameters in predictive models, where their real predictive power would be obtained [39][40][41].…”
Section: Discussionmentioning
confidence: 99%